Agathis bishopi (Nixon) (Hymenoptera: braconidae) its biology and usefulness as a biological control agent for false codling moth (FCM), Thaumatotibia leucotreta (Meyrick) (Lepidoptera: tortricidae), on citrus bishopi (Nixon) (Hymenoptera: braconidae) its biology and usefulness as a biological control agent for false codling moth (FCM), Thaumatotibia leucotreta (Meyrick) (Lepidoptera: tortricidae), on citrus - Gendall, Kierryn Leigh (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2008)
The false codling moth, Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae), is one of the major pests of citrus in South Africa, the others being mealybug, Mediterranean fruit fly, bollworm and some mites. Due to problems such as the expense of pesticides, insects evolving pesticide resistance (Hogsette 1999), chemical residue on the skin of export fruit and the negative impact of pesticides on the environment, it became necessary to find alternative methods for pest control (Viggiani 2000). Agathis bishopi (Nixon) (Hymenoptera: Braconidae), a larval parasitoid of false codling moth known only from the Sundays River Valley area (Sishuba 2003), offers a means of control for the pest. A total of 11 389 navel oranges were collected from various orchards in the Addo/Kirkwood area, and false codling moth larvae infested 36.09% of the fruit. A single parasitoid species, A. bishopi, was reared from these larvae. In 2006 the highest parasitism rate, 11.43%, was recorded in May and in 2007, the highest parasitism rate, 13.27%, was in April. Agathis bishopi parasitizes larvae in instars 2 and 3, possibly due to the accessibility of these younger instars to the female parasitoid and possibly due to the length of the life cycle of this koinobiont. Second instar hosts yielded the highest number of parasitoids, and there was no emergence of parasitoids from fifth instar larvae. Females of A. bishopi live for 18.5 days (n = 20; S.E. = 3.1) and males for 8.25 days (n = 20; S.E. = 1.23). Females produce an average of 23 offspring in a lifetime, while female false codling moths produce about 800 eggs each. A high number of parasitoids will be required per hectare to reduce the population of false codling moth. Captive rearing of A. bishopi proved difficult due to viral and fungal contamination. Agathis bishopi has potential for use in an integrated pest management programme once the hurdle of mass-rearing has been overcome.
Keywords: Cryptophlebia leucotreta -- Parasites; Cryptophlebia leucotreta -- Control; Pests -- Biological control; Tortricidae; Braconidae; Citrus -- Diseases and pests